"New Protean career Contract": Paradigma Baru Pengembangan Karir Abad 21 - Ririn Rachmawardini (Jurnal Manajemen Maranatha, 2005)
Current trends in organizational change have a psychological impact on individuals, and the result is increasing dislocation among people, opportunities, and mechanisms to connect them. The characteristics and attributes that typify a managerial career are shifting along with developments in organization structure. The competencies needed by a successful person in today’s organizations may be inadequate in the emerging organizational forms of the 21st century. A new model of career is quietly replacing the traditional corporate career model. This article identified the mix of competencies required for a successful career in organizations of 21st century. First, describe the new paradigm of career. Next, examine the phases to adapt new protean career. Finally, implications and directions for organization are discussed.